Cobb 700 response to increasing lysine by growth phase - L.D. Butler; C.G. Scanes; S.J. Rochell; A. Mauromoustakos; J.V. Caldas; C.A. Keen; C.W. Maynard; S.A. Bolden; R.D. Brister; P.A. Smith; R.E. Latham; C.M. Owens; et al. (Journal of Applied Poultry Research, 2020)
Summary: The Cobb MV × Cobb 700 male broiler was evaluated for BW and feed conversion ratio (FCR) when fed diets of increasing levels of digestible lysine (Lys) and ME within each growing phase (0–12 D, 12–26 D, 26–35 D, and 35–55 D). Male BW was highest (P < 0.0001) at 12 D of age for birds fed 1.24% digestible Lys and 3,194 ME vs. birds fed 1.20% digestible Lys and 3,084 ME. Male BW were also highest (P < 0.0001) at 26 D of age for birds fed 1.23% digestible Lys and 3,194 ME. However, birds were able to compensate with increased FCR (P < 0.0001) when fed diets with lower levels of digestible Lys and ME from 26 to 55 D to achieve similar BW (P > 0.05) compared with the birds on the highest level and duration of digestible Lys and ME. The control group, that is, industry standard digestible Lys and ME levels, had the lowest levels of digestible Lys and ME for the duration of the experiment and had the highest (P < 0.0001) FCR and the lowest (P < 0.0001) BW. The results for BW and FCR suggest that the digestible Lys needs are higher than previously established. More investigations within each growing phase should be performed to better define the requirements of the Cobb MV × Cobb 700 broiler for digestible Lys.